(untitled) (Indian Journal of Veterinary Pathology, 2026)
Canine mammary osteosarcoma is a rare but highly aggressive extra medullary tumour, predominantly affecting older female dogs and marked by rapid progression and a high metastatic potential. While histopathology is the standard diagnostic and prognostic tool, it does not always accurately represent the true proliferative activity of tumour cells, necessitating more sensitive adjunct techniques. Nucleolar organizer regions (NORs), which contain argyrophilic proteins involved in ribosomal RNA synthesis, can be visualized using silver staining (AgNOR). AgNOR quantification has emerged as a valuable adjunct to routine histopathology, as increased AgNOR counts correlate with higher metabolic activity, faster cell cycles, and greater tumour proliferation. Recent advances involving zinc and silver co-localization have further improved the sensitivity and consistency of AgNOR-based assessments. The present study investigated naturally occurring mammary gland osteosarcoma in bitches. Tumour tissues were collected, formalin-fixed, and subjected to routine histopathology, followed by AgNOR staining and zinc–silver co-localization analysis. Proliferative activity was evaluated through quantitative assessment of cell-cycle phases and mitotic figures. Results revealed a significant positive association between mitotic counts and proliferative phases of the cell cycle, along with a negative correlation with the G1 phase across all staining methods. These findings highlight the reliability of AgNOR techniques and zinc-silver co-localization as sensitive markers for assessing tumour proliferation and biological aggressiveness in canine mammary osteosarcoma.